RESPONS PERTUMBUHAN VEGETATIF SELEDRI (Apium graveolens L.) PADA BERBAGAI KOMPOSISI MEDIA TANAM - Immerson Limbong (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2020)
This study aims to determine the growth response and production of celery plants (Apium graveolus L.) on various growing media. The study was conducted at the Research Institute University of North Sumatra, with altitude of ± 32 meters above sea level starting in March 2019. This research was conducted using Non Factorial Randomized Block Design (RBD). The results showed that the treatment of planting media on celery plants did not significantly affect all.